Relationship between sexual dysfunction and quality of life in patients with Diabetes Mellitus (Research, Society and Development, 2025)
In recent years, in addition to the characteristic obstacles of Diabetes Mellitus, a new problem has been associated with this disease, sexual dysfunction. As a result, this study aimed to analyze the prevalence and effects of sexual dysfunction in adults diagnosed with Diabetes Mellitus. For this, a search was carried out in the PubMed/MEDLINE, SCOPUS and EMBASE databases. From the definition of inclusion and exclusion criteria, 32 results were selected from the 415 articles found to form the collection of this review, which portray the pathophysiology, prevalence and impacts of this disease on patients' quality of life. Diabetes Mellitus is responsible for sexual disorders due to the microvascular complications it causes. Furthermore, treatment for this health problem is hampered by the stigma of seeking treatment for sexual disorders, which leads to neglecting the search for help. Therefore, it is clear that multidisciplinary and intersectoral approaches must be carried out, such as the destigmatization of this issue in the social environment and preventive care measures for diabetic patients, as well as early screening of these patients with sexual disorders.